2017
DOI: 10.1021/acs.est.6b05149
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Determination and Characterization of Short-, Medium-, and Long-Chain Chlorinated Paraffins in Human Blood

Abstract: The industrial chlorinated paraffins (CPs) are comprised of short-chain (SCCPs), medium chain (MCCPs), and long chain (LCCPs) CPs. Although SCCPs and MCCPs are environmentally ubiquitous, little is known about CPs in humans. This study established a method for simultaneous determination of 261 SCCP, MCCP, and LCCP congener groups in one injection by reversed ultrahigh-pressure liquid chromatography coupled with chlorine-enhanced electron spray ionization-quadrupole time-of-flight mass spectrometry. The method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 38 publications
6
101
4
Order By: Relevance
“…9). MCCP concentrations measured in human placenta are slightly higher, MCCP concentrations measured in human blood 76 are around one order of magnitude higher than the measured MCCP concentrations in human breast milk. Studies on adverse effects of MCCPs in humans are missing, so it is currently impossible to assess the risk of MCCPs to humans.…”
Section: Mccp Concentrations In Mammalscontrasting
confidence: 54%
“…9). MCCP concentrations measured in human placenta are slightly higher, MCCP concentrations measured in human blood 76 are around one order of magnitude higher than the measured MCCP concentrations in human breast milk. Studies on adverse effects of MCCPs in humans are missing, so it is currently impossible to assess the risk of MCCPs to humans.…”
Section: Mccp Concentrations In Mammalscontrasting
confidence: 54%
“…LCCPs up to C 23 were also detected in human blood (up to 530 ng/g LW) from China. 14 These results indicate that LCCPs have a bioaccumulative potential, which highlights the importance of including LCCPs in the measurement of CPs.…”
Section: Resultsmentioning
confidence: 77%
“…Based on the relatively limited toxicity data available for LCCPs, they seem to be less toxic to organisms compared to SCCPs and MCCPs. 13 LCCPs have recently been detected in human blood (up to 530 ng/g lipid weight) 14 from China and in wildlife samples from China and Sweden with levels up to 10 μg/g lipid weight, whereby in one of the biota samples from Sweden LCCPs were dominant. 15,16 These findings may highlight the importance to include LCCPs in measurement programs for CPs.…”
Section: Introductionmentioning
confidence: 99%
“… 22 All CPs are persistent, 23 and they are bioaccumulative in humans. 24 , 25 Mammalian toxicity research has mostly focused on SCCPs 26 and has identified SCCPs as possible carcinogens to humans. 27 Although the toxicity of MCCPs and LCCPs has been studied less, MCCPs are considered to meet the REACH toxicity criteria, 28 and MCCP exposure has been shown to cause hemorrhaging effects in rats.…”
Section: Introductionmentioning
confidence: 99%